Jeremiah's scriptures : production, reception, interaction, and transformation - Najman, Hindy. (Supplements to the Journal for the Study of Judaism, 2016)
Jeremiah's Scriptures focuses on the composition of the biblical book of Jeremiah and its dynamic afterlife in ancient Jewish traditions. Jeremiah is an interpretive text that grew over centuries by means of extensive redactional activities on the part of its tradents. In addition to the books within the book of Jeremiah, other books associated with Jeremiah or Baruch were also generated. All the aforementioned texts constitute what we call "Jeremiah's Scriptures." The papers and responses collected here approach Jeremiah's scriptures from a variety of perspectives in biblical and ancient Jewish sub-fields. One of the authors' goals is to challenge the current fragmentation of the fields of theology, biblical studies, ancient Judaism. This volume focuses on Jeremiah and his legacy.